PERMAINAN TRADISIONAL SONLAH/ENGKLEK UNTUK PENINGKATAN SOSIAL EMOSIONAL ANAK USIA DINI - Evi Desmariani; Dr. Jendriadi; Tesya Cahyani Kusuma; Fenti Marfah Yanti (LP2M Universitas Adzkia, 2021)
The problem in this research is that the social emotional of Children is still not developing as expected, where in block play activities, children only want to play alone and do not allow their friends to participate in helping, then the children choose friends to play with him, and in playing children don’t follow the rules and don’t want to queue up to wait their turn. For this reason, researchers are interested in improving children’s social emotional through the tradisional sonlah/engklek game. The purpose of this study is to describe the improvement of children’s social emotional trough traditional sonlah/engklek game. The Research method used is a qualitative method with a literatur approach with data collection techniques and data sources obtained from reference books and journals relevant to the Research problem. After obtaining the required data , then the data will be analyzed by connecting the problem with relevant concepts and theories. The results of the research obtained from this study indicated that the traditional sonlah/engklek game is a folk game that is usually played together or in groups so that the traditional sonlah/engklek game can improve aspects of children’s social emotional such as having skills in working together, skills in adapting interacting, adaptibility, self-control, skills in empathy, obeying rules, and skills in respecting others. So in this study it can be concluded that the social emotional of children can be improved through the traditional sonlah/engklek game